2010
DOI: 10.1002/jnr.22416
|View full text |Cite
|
Sign up to set email alerts
|

BDNF‐Akt‐Bcl2 antiapoptotic signaling pathway is compromised in the brain of autistic subjects

Abstract: Although the pathogenesis of autism is not understood, emerging evidence points to apoptotic mechanisms being involved in this disorder. However, it is not known whether apoptosis signaling is deregulated in the brain of autistic subjects. This study investigates how the apoptosis-related proteins are regulated in the autistic brain. Our studies show that Bcl2 is significantly decreased, whereas the expression of p53 is increased, in the brain of autistic subjects in comparison with age-matched controls. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 29 publications
8
82
0
Order By: Relevance
“…47,48 Previously, we found that the apoptosis-related proteins Bcl-2, p53, and cathepsin D are altered in both the brain and the lymphoblasts of autistic subjects. 4,32,49 The pathogenesis of autism may involve enhanced apoptosis in the brain and lymphoblasts. It is possible that the down-regulation of FAK-Src activities may contribute to an alteration of apoptosisrelated proteins in autism.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Previously, we found that the apoptosis-related proteins Bcl-2, p53, and cathepsin D are altered in both the brain and the lymphoblasts of autistic subjects. 4,32,49 The pathogenesis of autism may involve enhanced apoptosis in the brain and lymphoblasts. It is possible that the down-regulation of FAK-Src activities may contribute to an alteration of apoptosisrelated proteins in autism.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Studies have linked p53 to developmental abnormalities 13 (see also Supplemental Table 5), and regions adjacent to 17p13.1 encoding for proteins with important roles in brain function and neurodevelopment (eg, axonal dynein heavy chain 2 and Na + /K + ATPase subunit β-2) and others have been found to be associated with autism (AU) (eg, ephrin-B3 14 ). Increased p53/Bcl2 protein ratios had been found in brain regions of a small set of autistic subjects [15][16][17] ; however, no characterization of posttranslational modifications or functional status of p53 was undertaken. Neuronal Pten haploinsufficiency in mice results in a sustained Akt activation and decreased p53 protein expression and function (evidenced by downregulation of p53 targets), mitochondrial dysfunction, accumulation of mtDNA deletions, 6 and the occurrence of aberrant social and repetitive behavior associated with AU.…”
mentioning
confidence: 99%
“…p53 values increased by 130% over those in the postmortem parietal cortex blocks of patients with autism [21]. In another report, p53 levels increased by 67.5% and 38% in the superior frontal and cerebellar cortices of patients with autism, respectively [22].Sheikh et al [23] found an increased p53 expression in the Purkinje and granule cells of the cerebella in people with autism compared with age-matched controls. These findings suggest that deranged apoptotic mechanisms involved in the pathogenesis of patients with autism.…”
Section: Apoptotic Factorsmentioning
confidence: 92%